A 32 full factorial design for optimizing the ocular retention of bromfenac sodium using thermo sensitive in situ gel - JAKIRHUSSAINMUSTAQ SHAIK; MOUNIKA VEGESNA; CHANDANA ROJA; SWATHI PUTTA; BHAVANI BODDEDA (International Journal of Pharma and Bio Sciences, 2017)
The main aim of the present work is to formulate and evaluate anophthalmic drug delivery system of bromfenac sodium using suitable gelling polymers by cooling technique. For elucidating the effect of formulation factors of press coated tablets a 32 full factorial design was employed. The effect of two factors, amount of gelling agent (X1) and amount of viscosity enhancer (X2) as independent variables were studied on dependent variables Y1 (gelling capaciy), Y2(gelation temperature) and Y3 (Cumulative % drug release). The prepared in situ gelwere evaluated for clarity, pH, gelling capacity, gelation temperature, viscosity, drug content, in vitro drug release and kinetics studies.All the formulations were clear, transparent and yellow.The pH of the formulations ranges from 7.01-7.34 which is an acceptable range when compared with the eye pH of 7.4.Gelation temperature was between 37-43.5°C for all the formulations.The gelling capacity of the formulations was found to be between 4-10 hr. All the formulations follow pseudo plastic behaviour (shear thinning systems). This property is very useful during the inter blinking of the eye. A shear thinning ophthalmic system does not cause any inconvenience to the patient.Drug content of all the formulations was in between 95.13-98.55 %.In vitro drug release of the formulations was decreased when the amount of gelling agent and viscosity enhancer was increased.The optimum formulation consisting of bromfenac (90mg), poloxamer 188 (15g) and HPMC E5 (1.75g) exhibited gelling capacity of 7.12 h, gelling temperature of 37.02 °C and cumulative % drug release of 98.19 % in 12 h. Bromfenac sodium in situ gel exhibited biphasic release profile obeying zero order release kinetics following non-Fickian diffusion mechanism.